Bubble Economy in Financial Markets and Digital Platforms: Regulatory Challenges and Policy Directions for Indonesia - Umar Hamdan Nasution (Universitas Dharmawangsa Medan, 2026)
This policy article examines the evolution of economic bubbles from classical financial markets to digitally driven bubbles shaped by information architecture and social media algorithms. The study aims to formulate policy directions relevant to Indonesia by integrating economic theory, empirical evidence, and institutional regulatory analysis. Using a qualitative policy review approach, the article synthesizes classical bubble theories, digital economy literature, documented case studies, and Indonesian regulatory frameworks. The findings indicate that Indonesia possesses relatively strong macroprudential and market-conduct instruments to address classical financial bubbles. However, significant regulatory gaps persist in governing digital bubbles emerging from platform-based amplification mechanisms. This article proposes a structured policy recommendation matrix emphasizing algorithmic accountability, inter-agency coordination, UMKM protection, and adaptive financial governance. Keywords: Bubble Economy, Digital Platforms, Indonesia, Policy Analysis, Regulation, Social Media